ANALISIS PENGARUH ENTERPRISE RISK MANAGEMENT (ERM) DAN GOOD CORPORATE GOVERNANCE (GCG) TERHADAP NILAI PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2017-2019 - Yusrina Almas Sajida; Agung Purwanto (Diponegoro Journal of Accounting, 2021)
The purpose of this research is to examine the effect of enterprise risk management, good corporate governance and firm value, as well as the effect of firm size and leverage in the relationship between risk management, good corporate governance and firm value in financial sector companies. The variables used in the test are enterprise risk management, managerial ownership, institutional ownership, independent commissioners, and audit committees as independent variables, and firm value as the dependent variable. Furthermore, this study uses firm size and leverage as control variables. The sample in this study used banking sector companies listed on the Indonesia Stock Exchange in 2017-2019 with total sample of 111 samples. The data used in this research is secondary data which was obtained through the purposive sampling method. The analytical technique used for examining the hypothesis is through multiple linear regressions.The empirical results of this research shows that ERM, managerial ownership, institutional ownership, and independent commissioners are indicated to have a significant positive effect on firm value. Meanwhile, there was no indication of a significant influence of the audit committee on firm value. Based on these results, it can be stated that the implementation of ERM and GCG in a company has a positive effect on firm value.